Voices from the Mississippi hill country : the Benton County civil rights movement - DeBerry, Roy; Futorian, Aviva; Klein, Stephen, 1936-; Lyons, John, 1981- (University Press of Mississippi, 2020)
"Voices from the Mississippi Hill Country is a collection of interviews with residents of Benton County, Mississippi-an area with a long and fascinating civil rights history. The product of more than twenty-five years of work by the Hill Country Project, this volume examines a revolutionary period in American history through the voices of farmers, teachers, sharecroppers, and students. No other rural farming county in the American South has yet been afforded such a deep dive into its civil rights experiences and their legacies. These accumulated stories truly capture life before, during, and after the movement. The authors' approach places the region's history in context and reveals everyday struggles. African American residents of Benton County had been organizing since the 1930s. Citizens formed a local chapter of the NAACP in the 1940s and '50s. One of the first Mississippi counties to get a federal registrar under the 1965 Voting Rights Act, Benton achieved the highest per capita total of African American registered voters in Mississippi. Locals produced a regular, clandestinely distributed newsletter, the Benton County Freedom Train. In addition to documenting this previously unrecorded history, personal narratives capture pivotal moments of individual lives and lend insight into the human cost and the long-term effects of social movements. Benton County residents explain the events that shaped their lives and ultimately, in their own humble way, helped shape the trajectory of America. Through these first-person stories and with dozens of captivating photos covering more than a century's worth of history, the volume presents a vivid picture of a people and a region still striving for the prize of equality and justice"--